Implementation of Written Assessment Higher Order Thinking Skills in Physical Learning with a Scientific Approach based Blended Learning - Chandra Ertikanto; I Wayan Distrik; I Dewa Putu Nyeneng (Jurnal Pembelajaran Fisika, 2022)
This study aims to describe: (1) the effectiveness of HOTS in physics learning with a blended learning-based scientific approach, (2) the efficiency of the suitability of learning objectives of physics through a blended learning-based scientific approach with HOTS written assessment, and (3) safety through teacher responses to written assessments. HOTS through a scientific approach based on blended learning in physics learning. The design of this research is the implementation stage of continually development research from 2019 which has gone through the stages of product testing and extensive testing, which focus on Senior High Schools in Bandar Lampung City, Lampung Province during the Covid-19 pandemic. The sample used in this study was 36 students of SMAN 9 Bandar Lampung with a purposive sampling technique. The research instrument used was the HOTS Written Assessment with multiple choices of 20 questions. Data analysis techniques are carried out qualitatively. Conclusion: (1) The results of the effectiveness test were 83,33% of students passed the KKM, and the highest score was 97,5. (2) The efficiency of the suitability of the learning objectives of Physics through a blended learning-based scientific approach with HOTS written assessment, is very efficient in use, and (3) The safety of HOTS written assessments through a blended learning-based scientific approach in physics learning is very meaningful.Keywords: Assessment, Higher order thinking skills, Scientific ApproachDOI: http://dx.doi.org/10.23960/jpf.v10.n1.202202